2011
DOI: 10.1891/0739-6686.29.227
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genomics of Type 2 and Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy and the prevalence of GDM is increasing worldwide. Short- and long-term complications of GDM on mothers and fetuses are well-recognized. These include more than seven-fold higher risk for type 2 diabetes mellitus (T2DM) later in life in women with GDM than those without. Evidence supports that GDM shares several risk factors with T2DM, including genetic risks. This chapter reviewed studies on candidate genes shared by T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 98 publications
(168 reference statements)
0
8
0
1
Order By: Relevance
“…GDM, caused by environmental and genetic factors, as well as gene-environment interactions, shares similar pathophysiological features to T2DM, such as glucose intolerance, insulin resistance, and impaired pancreatic β-cell function [5][6][7]. Furthermore, several studies have revealed that women with GDM history are more likely to develop T2DM.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…GDM, caused by environmental and genetic factors, as well as gene-environment interactions, shares similar pathophysiological features to T2DM, such as glucose intolerance, insulin resistance, and impaired pancreatic β-cell function [5][6][7]. Furthermore, several studies have revealed that women with GDM history are more likely to develop T2DM.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Although the exact pathophysiology of GDM is still unclear, it is generally believed that GDM and T2DM share the same underlying pathologic mechanisms, including insulin resistance and β-cell dysfunction leading to metabolic changes [ 5 ]. In addition, T2DM is a multifactorial disease and GDM may share genetic risk factors with T2DM [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…GDM affects 1-14% of all pregnancies; this wide variation seems to reflect the different distributions of genetic and epigenetic factors as well as environmental risk [2]. The offspring of patients with GDM has a greater incidence of perinatal complications including birth defects in nervous, cardiovascular, and genitourinary system [3,4]. Research in the past decade confirmed that GDM is correlated to obesity, ethnicity, maternal age, family history of diabetes, and genetic predisposition [5].…”
Section: Introductionmentioning
confidence: 99%